2021
DOI: 10.1101/2021.06.15.448181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mineral crystal thickness in calcified cartilage and subchondral bone in healthy and osteoarthritic knees

Abstract: Osteoarthritis (OA) is the most common joint disease globally. In OA, articular cartilage degradation is often accompanied with sclerosis of the subchondral bone. However, the association between OA and tissue mineralization at the nanostructural level is currently not understood. Especially, it is technically challenging to identify calcified cartilage, where relevant but poorly understood pathological processes like tidemark multiplication and advancement occur. Here, we used state-of-the art micro-focus sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…On one side, there is a layer of articular cartilage (AC) with depth-dependent gradients in fibre orientation (first described by the Benninghof architecture [ 7 ]), type II collagen/proteoglycan content ratios, and hydration [ 8 ], and (more recently identified) nanoscale collagen fibrillar pre-strain and intramolecular disorder [ 9 ]. As shown in Fig 1 , collagen fibrils in the AC traverse a tidemark into a layer of calcified cartilage (CC) [ 10 , 11 ], enabling a firm anchorage of the AC cartilage to the underlying subchondral bone (SCB). Below the SCB is the more open spongy or trabecular bone (TB) network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one side, there is a layer of articular cartilage (AC) with depth-dependent gradients in fibre orientation (first described by the Benninghof architecture [ 7 ]), type II collagen/proteoglycan content ratios, and hydration [ 8 ], and (more recently identified) nanoscale collagen fibrillar pre-strain and intramolecular disorder [ 9 ]. As shown in Fig 1 , collagen fibrils in the AC traverse a tidemark into a layer of calcified cartilage (CC) [ 10 , 11 ], enabling a firm anchorage of the AC cartilage to the underlying subchondral bone (SCB). Below the SCB is the more open spongy or trabecular bone (TB) network.…”
Section: Introductionmentioning
confidence: 99%
“…Below the SCB is the more open spongy or trabecular bone (TB) network. Scanning X-ray scattering and electron microscopy measurements on the calcified mineral phase in the calcified plate (CP) (the combined calcified cartilage and subchondral bone), have revealed gradients in mineral composition [ 12 ], crystallinity, and size [ 10 ], and recently, differences in the mineral crystallite thickness between healthy and osteoarthritic patients [ 11 , 13 ]. The gradient in compressive properties from cartilage (1-10MPa) to subchondral bone (GPa) reduces high interfacial shear stresses which could otherwise lead to cracks and delamination between the softer cartilage and the stiffer bone.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, we have limited our sampling to a specific condylar anatomical site in the metacarpophalangeal joint and given that in-vivo strains vary across the joint, it would be interesting to test if nanomechanical parameters like pre-strain shows a correlation with varying physiological force levels across the joint. Lastly, we have not yet considered changes in OA and ageing, to establish a baseline characterisation of the normal BCI in an animal model; a recent study [11] has shown that nanoscale mineral particle thickness is significantly different in OA versus normal human patients and investigating in situ mechanical response in aged human cartilage would no doubt be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Below the subchondral bone is the more open spongy or trabecular bone network. Scanning X-ray scattering and electron microscopy measurements on the calcified mineral phase in the calcified plate (the combined calcified cartilage and subchondral bone) have revealed gradients in mineral composition [12], crystallinity, and size [10], and recently, differences in the mineral crystallite thickness between healthy and osteoarthritic patients [11,13]. The gradient in compressive properties from cartilage (1-10MPa) to subchondral bone (GPa) reduces high interfacial shear stresses which could otherwise lead to cracks and delamination between the softer cartilage and the stiffer bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation